POTENSI LOKAL USAHA PANDEBESI DESA TENGGILISREJO KABUPATEN PASURUAN - Ascosenda Ika Rizqi; Eva Mufidah; Vita fibriyani; M.T Ghifary (LP2M STP Mataram, 2021)
One of the Tri Dharma College activities is community service which provides learning and working experiences in activities to increase potential for the community. Blacksmith is a job that is done manually using human power using metal raw materials. Metal technology is included as extractive technology, namely technology which in the process reduces, from the basic ingredients of metal technology in general, is an indicator of the development of high civilizations that humans have achieved. then reduced to the form of artifacts. The Pande Besi Small Industry Center can be found in the Nguling District and Gondangwetan District, Pasuruan Regency. Some Pandebesi SMEs went out of business because there were no more successors, on the other hand because of uncertain income and not easy in the manufacturing process.